SPECIFICS OF SOCIAL AND CULTURAL PROJECTS REALIZATION IN MODERN RUSSIA (Revista Inclusiones, 2020)
In Russia, state cultural institutions play a crucial role in forming and meeting the cultural needs of society, creating conditions and technologies for the comprehensive development and creative selfrealization of personality, ensuring active cultural leisure activity, and maintaining the proper level of culture as a material and spiritual environment for human existence. Various socio-cultural projects that have spread widely in Russia in recent decades are developed and implemented for these purposes. The goal of the present study is to identify the specific characteristics of the realization of socio-cultural projects in the cultural institutions of Moscow. Socio-cultural projects that had been realized in the cultural institutions of Moscow in the 2000s serve as the object of the study. The study methods comprise theoretical analysis of project documents, the practices of formation and realization of socio-cultural projects in the cultural institutions of Moscow, as well as practical participation in the measures and projects of cultural institutions and the development of sociocultural programs. The study concludes that the projects and programs of district cultural institutions are actualized by specific social problems of individual social groups (children, adolescents, adults, and pensioners). The main direction of socio-cultural activity aimed at resolving social problems is the organization of psychological support for families in solving family problems. Further improvement of sociocultural activity can be achieved through restructuring the content and forms of said activity in the direction of strengthening its social targeting.